Ex 5.5, 11 - Chapter 5 Class 12 Continuity and Differentiability
Last updated at Dec. 16, 2024 by Teachoo
Ex 5.5
Ex 5.5, 2
Ex 5.5, 3 Important
Ex 5.5, 4
Ex 5.5, 5
Ex 5.5,6 Important
Ex 5.5, 7 Important
Ex 5.5, 8
Ex 5.5, 9 Important
Ex 5.5, 10 Important
Ex 5.5, 11 Important You are here
Ex 5.5, 12
Ex 5.5, 13
Ex 5.5, 14 Important
Ex 5.5, 15
Ex 5.5, 16 Important
Ex 5.5, 17 Important
Ex 5.5, 18
Last updated at Dec. 16, 2024 by Teachoo
Ex 5.5, 11 Differentiate the functions in, γ(π₯ πππ β‘π₯ ) γ^π₯ + γ(π₯ π ππβ‘π₯ ) γ^(1/π₯)π¦ = γ(π₯ πππ β‘π₯ ) γ^π₯ + γ(π₯ π ππβ‘π₯ ) γ^(1/π₯) Let π’ = γ(π₯ πππ β‘π₯ ) γ^π₯ , π£ = γ(π₯ π ππβ‘π₯ ) γ^(1/π₯) π¦ = π’+π£ Differentiating both sides π€.π.π‘.π₯. ππ¦/ππ₯ = (π (π’ + π£))/ππ₯ ππ¦/ππ₯ = ππ’/ππ₯ + ππ£/ππ₯ Calculating π π/π π π’ =γ (π₯ πππ β‘π₯ ) γ^π₯ Taking log both sides . logβ‘π’ = logγ (π₯ πππ β‘π₯ ) γ^π₯ logβ‘π’ = π₯ . log (π₯ πππ β‘π₯ ) Differentiating both sides π€.π.π‘.π₯. π(logβ‘π’ )/ππ₯ = (π(π₯ . logβ‘(π₯ cosβ‘π₯ ) ) )/ππ₯ π(logβ‘π’ )/ππ’ . ππ’/ππ₯ = (π(π₯ . logβ‘(π₯ cosβ‘π₯ ) ) )/ππ₯ 1/π’ (ππ’/ππ₯) = (π(π₯ . logβ‘(π₯ cosβ‘π₯ ) ) )/ππ₯ (As πππβ‘(π^π )=π . πππβ‘π) Using product Rule As (π’π£)β = π’βπ£ + π£βπ’ 1/π’ (ππ’/ππ₯) = ππ₯/ππ₯ logβ‘γ(π₯ πππ π₯)γ+π₯ (π(πππβ‘(π₯ πππ β‘π₯ ) ) )/ππ₯ 1/π’ (ππ’/ππ₯) = logβ‘γ(π₯ cosβ‘π₯)γ+π₯/(π₯ cosβ‘π₯ ) Γ (π₯ πππ π₯)^β² 1/π’ (ππ’/ππ₯) = logβ‘γ(π₯ cosβ‘π₯)γ+1/cosβ‘π₯ Γ (1.cosβ‘π₯+π₯(βsinβ‘π₯ )) 1/π’ (ππ’/ππ₯) = logβ‘γ(π₯ cosβ‘π₯)γ+((cosβ‘π₯ β π₯ sinβ‘π₯ ))/cosβ‘π₯ 1/π’ (ππ’/ππ₯) = logβ‘γ(π₯ cosβ‘π₯)γ+cosβ‘π₯/cosβ‘π₯ β(π₯ sinβ‘π₯)/cosβ‘π₯ 1/π’ (ππ’/ππ₯) = logβ‘γ(π₯ cosβ‘π₯)γ+1βπ₯ π‘ππ π₯ ππ’/ππ₯ = u (1βπ₯ tanβ‘π₯+logβ‘γ(π₯ cosβ‘π₯ γ)) Putting value of π’ ππ’/ππ₯ = (π₯ cosβ‘π₯ )^π₯ (1βπ₯ tanβ‘π₯+πππβ‘(π πππβ‘π ) ) Calculating π π/π π π£=γ(π₯ π ππβ‘π₯ ) γ^(1/π₯) Taking log both sides logβ‘π£=logβ‘γ γ(π₯ π ππβ‘π₯ ) γ^(1/π₯) γ logβ‘π£= 1/π₯ log (π₯ π ππβ‘π₯ ) Differentiating both sides π€.π.π‘.π₯. (π(logβ‘π£))/ππ₯ = π(1/π₯ " . " )/ππ₯ (π(logβ‘π£))/ππ£ . ππ£/ππ₯ = (1/π₯ .logβ‘(π₯ sinβ‘π₯ ) )^β² 1/π£ Γ ππ£/ππ₯ = (1/π₯ .logβ‘(π₯ sinβ‘π₯ ) )^β² 1/π£ Γ ππ£/ππ₯ = (((logβ‘γ(π₯ sinβ‘π₯)γ )^β² π₯ + π₯^β² logβ‘γ(π₯ sinβ‘π₯)γ)/π₯^2 ) Using quotient rule (π’/π£)^β² = (π’^β² π£ β π£^β² π’)/π£^2 Where u = log (x sin x) , v = x 1/π£ Γ ππ£/ππ₯ = 1/x^2 ((logβ‘γ(π₯ sinβ‘π₯)γ )^β² π₯ + logβ‘γ(π₯ sinβ‘π₯)γ ) 1/π£ Γ ππ£/ππ₯ = 1/x^2 ([1/(π₯ sinβ‘π₯ ) \ Γ(π₯ sinβ‘π₯ )^β² ]π₯ + logβ‘γ(π₯ sinβ‘π₯)γ ) 1/π£ Γ ππ£/ππ₯ = 1/x^2 (1/sinβ‘π₯ \ Γ(π₯ sinβ‘π₯ )^β²+ logβ‘γ(π₯ sinβ‘π₯)γ ) 1/π£ Γ ππ£/ππ₯ = 1/π₯^2 (((1 . π ππβ‘π₯ + π₯ πππ β‘π₯))/π ππβ‘π₯ \ + πππβ‘γ(π₯ π ππβ‘π₯)γ ) 1/π£ Γ ππ£/ππ₯ = 1/π₯^2 (((π ππβ‘π₯ + π₯ πππ β‘π₯))/π ππβ‘π₯ \ + πππβ‘γ(π₯ π ππβ‘π₯)γ ) 1/π£ Γ ππ£/ππ₯ = 1/π₯^2 (1+π₯ cotβ‘π₯+ πππβ‘γ(π₯ π ππβ‘π₯)γ ) ππ£/ππ₯ = π£((1 + γπ₯ πππ‘γβ‘γπ₯ γ β πππβ‘γ (π₯ π ππβ‘π₯ ) γ)/π₯^2 ) ππ£/ππ₯ = (π₯ π ππβ‘π₯ )^(1/π₯) ((1 + γπ₯ πππ‘γβ‘γπ₯ γβ πππ (π₯ π ππβ‘π₯ ))/π₯^2 ) Now, ππ¦/ππ₯ = ππ’/ππ₯ + ππ£/ππ₯ Putting value of ππ’/ππ₯ & ππ£/ππ₯ π π/π π = (π πππβ‘π )^π (π β π πππβ‘π+πππβ‘(π πππβ‘π ) ) + (π πππβ‘π )^(π/π) ((γπ πππγβ‘γπ γ + π β π₯π¨π (π πππβ‘π ))/π^π )